Strategi Membangkitkan Kembali Usaha Pupuk Organik Padat di Simantri 103 Serongga Kelod, Desa Serongga, Kecamatan Gianyar, Kabupaten Gianyar - KOMANG BELY SETYAWATI; I GEDE SETIAWAN ADI PUTRA; KETUT SURYA DIARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Strategies to Promote Organic Solid Fertilizer Business in Simantri 103 of Serongga Kelod, Serongga Village, Gianyar Sub-District, Gianyar Regency Integrated Farming System (Simantri) is one of the leading programs of Bali Provincial Government to improve agriculture in order to support the Bali Mandara program. The purpose of this research is to investigate the internal and external environment factors found in solid organic fertilizer business at Simantri 103 of Serongga Kelod, Serongga Village, Gianyar Subdistrict, Gianyar Regency and to analyze the strategy to revive solid organic fertilizer business at Simantri 103 Serongga Kelod, Serongga Village, Sub-District of Gianyar, Gianyar Regency. Results of internal factor analysis of Simantri 103: a) strength (availability of adequate raw material and ownership of organic fertilizer processing facility is the most influential factor) b) weakness (lack of capital and lack of land of organic fertilizer processing in Simantri still become the main factor of weakness at Simantri 103). External factors: a) opportunities (development of organic fertilizer business in Simantri is an important factor) b) threat (competition with inorganic fertilizers is a threat in the development of solid organic fertilizer business). Based on the SWOT analysis, it was found that the alternative strategy that became the priority was the strategy to revive or improve the production of solid organic fertilizer. QSPM analysis results show that the strategy that has the biggest attraction score is the product development strategy. Suggestions that can be given is to fix the biggest weaknesses such as lack of capital and to pay attention to opportunities such as the trust of the financial institution.